Awards' night '97 - Council of Student Organizations - De La Salle University, Manila (Animo Repository, 1997)
The Council of Student Organizations (CSO) named 11 teachers for this year's Students' Search for Outstanding Teachers (SSOT) at the Awards' Night '97. The Awards Night also recognizes The Outstanding Coed-The Outstanding Young Men (TOC-TOYM) in DLSU. The Harvest of Winners gave an awards to Outstanding Vice-President, Secretary and Treasurer of the different Organizations.